2020
DOI: 10.14744/semb.2020.03453
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Diverticulum Localization and Hinchey Classification on Recurrence and Complications in Acute Colonic Diverticulitis

Abstract: Objectives: Diverticular disease of the colon is a pathology that arises from outward ballooning of the mucosa due to some weakness in the muscle layer. Diverticular disease may range from symptomatic uncomplicated diverticular disease to symptomatic disease with complications, such as acute diverticulitis or diverticular bleeding. Acute colonic diverticulitis occurs in about 10- 25% of patients. Methods: In this study, 134 patients who were admitted to our emergency cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…There are also studies showing that the localization of the diverticulum may be one of the factors that may play a role in the severity and recurrence of the disease. [ 24 ] In our study, 95% of the patients had diverticulitis located in the sigmoid colon. In 65% of the patients, the diverticula are found only in the sigmoid colon and in 24% in other parts of the colon together with the sigmoid colon.…”
Section: Discussionmentioning
confidence: 54%
“…There are also studies showing that the localization of the diverticulum may be one of the factors that may play a role in the severity and recurrence of the disease. [ 24 ] In our study, 95% of the patients had diverticulitis located in the sigmoid colon. In 65% of the patients, the diverticula are found only in the sigmoid colon and in 24% in other parts of the colon together with the sigmoid colon.…”
Section: Discussionmentioning
confidence: 54%
“…Additionally, we found that right sided diverticular location was associated with a higher occurrence of diverticulitis (OR 1.97, P = 0.02), as their BMI was significantly higher than patients with right sided colonic diverticulosis but without diverticulitis (31.1 vs. 28.2 kg/m 2 , respectively, P = 0.01). Previous study reported that rectosigmoid location is an important factor for recurrence and for acute diverticulitis prognosis [29]. Therefore, further studies are needed to accurately assess diverticulosis location on the rate and prognosis of diverticulitis.…”
Section: Discussionmentioning
confidence: 98%
“…Understanding the pattern of complication presentation and successful medical management in this younger population can help guide treatment algorithms that can help prevent unnecessary intervention. This differentiation is vital in the process of developing treatment guidelines for diverticulitis in patients under 40 years, as the common treatments for complicated vs uncomplicated diverticulitis vary drastically in terms of invasiveness, hospitalization length-of-stay, and cost of treatment [ 15 ].…”
Section: Discussionmentioning
confidence: 99%